POLA HIDUP PENDERITA HIPERTENSI KHUSUSNYA MASYARAKAT NELAYAN PESISIR PANTAI DI DESA ONGKA - Noviany Banne Rasiman (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2022)
Hypertension is a disease that has a character with the term silent killer because the disease can damage organ systems progressively, patently resulting from the consequences such as stroke, heart problems, and kidney damage, which have the potential to cause death in a person (Erkoc , et al., 2016). The prevalence of hypertension in Central Sulawesi is known to be 916,344 people or 34.1% in 2019. In the Parigi Moutong Regency, the number of cases of hypertension since 2017, the prevalence of hypertension is 7,464 people and as many as 71,934 people in 2019, as well as those who get hypertension. health services is only 12.7%. The purpose of this study is to find out the lifestyle of coastal fishing communities who suffer from hypertension in Ongka Village The research design is quantitative research using a questionnaire. The research variable is the lifestyle of hypertension sufferers in coastal fishing communities. The population in this study amounted to 1,174 people. The sample is 88 people. The results showed that the lifestyle of fishing communities who suffered from hypertension was found to be at risk with a percentage of 46.6% and those who were not at risk were found to be 53.4%. The conclusion of this study is that the coastal community of Ongka Village already has a lifestyle that is not at risk and triggers the prevalence of hypertension. .